Celebrity Endorser dalam Meningkatkan Kepercayaan Masyarakat pada Vaksin Covid-19 - Dina Novita; Erni Widiastuti; Asih Handayani (MARGIN ECO, 2022)
The acceptance of the Indonesian people for the Covid-19 vaccine is inseparable from the diverse information received by the public, so it is important to increase public confidence in the Covid-19 vaccine through the celebrity endorser strategy. This study aims to determine the effectiveness of celebrity endorsers in increasing public confidence in the Covid-19 vaccine. This research was conducted with a descriptive design through a qualitative approach. Data were collected by researchers through documentation and literature study and data analysis was carried out using an interactive model. The results showed that endorsing celebrities is a method of promoting or communicating to the public by utilizing celebrities. The image and character possessed by celebrities are believed to be able to attract people to carry out the same behavior. The existence of celebrities as endorsers is quite effective in increasing public confidence in the Covid-19 vaccine. Based on data on the daily number of Covid-19 vaccine recipients up to March 28, 2021, it shows that the total number of recipients of the Dose I vaccine is 7.24 million, so the government is expected to understand the character of celebrities who can work together in increasing the success of government programs, including adjusting the program, government with individual and social identities attached to celebrities. Keywords: celebrity endorser, vaccine, public trust.